Indonesia’s Blue Economy Initiative: Rethinking Maritime Security Challenges - Dinarto, Dedi (2017)
Indonesian officials are eager to harness the blue economy initiative. This notwithstanding, there are numerous other non-traditional maritime security challenges like IUU fishing, piracy, and marine plastic debris that impede on its progress. Good maritime security governance thus plays an important role.